Limited effect of radial oxygen loss on ammonia oxidizers in Typha angustifolia root hairs - Hernández-Del Amo, Elena; Dolinová, Iva; la Ramis-Jorba, Gal; Gich, Frederic; Bañeras, Lluís (Scientific reports, 2020)
The benefits of plant-microbe interactions have been exploited extensively for nutrient removal. Radial oxygen loss in aquatic macrophytes potentially promotes nitrification and accelerates nitrogen removal through coupled nitrification-denitrification process. Nitrification is likely the limiting activity for an effective nitrogen removal in wetlands. In this work, we have quantified the effect of radial oxygen losses in Typha angustifolia plants in environments of contrasting salinities, including a temporary lagoon, a constructed wetland, and a river estuary. In all sites, radial oxygen diffusion occurred mainly at a narrow band, from 1 to 5 cm from the root tip, and were almost absent at the tip and basal sections of the root (> 5 cm). Root sections with active oxygen diffusion tended to show higher bacterial and archaeal densities in the rhizoplane according to 16S rRNA gene abundance data, except at higher salinities. Archaeal amoA /bacterial amoA gene ratios were highly variable among sites. Archaeal nitrifiers were only favoured over bacteria on the root surface of Typha collected from the constructed wetland. Collectively, radial oxygen loss had little effect on the nitrifying microbial community at the smaller scale (differences according to root-section), and observed differences were more likely related to prevailing physicochemical conditions of the studied environments or to long-term effects of the root microenvironment (root vs sediment comparisons).
Keywords: mikrobiota; nitrifikace; kořeny rostlin; Plant Roots; RNA ribozomální 16S; Typhaceae; Oxygen; kyslík; Ammonia; Nitrification; Microbiota; amoniak; orobincovité; RNA, Ribosomal, 16S